The memory library [large type] - Storey, Kate (Thorndike Press large print top shelf., 2024)
"Each year, on her daughter's birthday, she adds a new book to her shelves - with a note in the front dedicated to her own greatest work. But Ella - Sally's only child - fled to Australia twenty-one years ago after a heated exchange, and never looked back. And though Sally still dutifully adds a new paperback to the shelves every time the clock strikes midnight on July 11th, her hopes of her daughter ever thumbing through the pages are starting to dwindle. Then disaster strikes and Ella is forced to return to the home she once knew. She is soon to discover that when one chapter ends, another will soon follow."--Amazon.